Factors Affecting English Language Learning in English as a Foreign Language (EFL) Context: A Literature Review Study - Urip Sulistiyo (IJER (Indonesian Journal of Educational Research), 2018)
This study is part of larger research investigating students’ preferred activities in learning English both inside and outside the classrooms in English as a Foreign Language Context (EFL). Some relevants issues regarding the theories of teaching and learning English were presented and reviewed in this study. This literature review study provided a brief snapshot to the importance of knowing the students’ preferred activities in their efforts to learn English as a foreign language in Indonesia. This review also described the researcher’s experience in learning and teaching English as the background of this study. In addition, it summarized the significance of the study to improve the English teaching and learning practice at University level in Indonesia, in particular, for non-English Department students.